Peningkatan Kompetensi Guru Madrasah Ibtidaiyah Melalui Pemanfaatan Artificial Intelligence dan Digitalisasi Pembelajaran - Yufi Mohammad Nasrullah, Yufi Mohammad Nasrullah; Hilda Ainissyifa; Dadang Muliawan; Sopa Siti Marwah; Nurul Fatonah; Rangga Azyan (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2025)
This community service program aims to improve the competency of elementary school teachers in utilizing Artificial Intelligence (AI) and digitalizing learning in Limbangan District, Garut Regency. Digital transformation requires teachers to have technological literacy beyond basic skills, but field findings indicate that MI teachers' digital competency remains at a low level, especially in AI integration, digital learning design, and interactive media production. The activity was carried out through a Participatory Action Research (PAR) approach that involved teachers as active partners in the know, understand, plan, act, reflect, and evaluate stages. A total of 30 teachers from 10 MIs were involved in practice-based training, mentoring, learning simulations, and AI-based media production. Data were obtained through pretests and posttests, observations, interviews, and structured reflections. The program results showed a significant increase in teachers' understanding and skills in using AI-based tools (ChatGPT, Gemini, Canva AI) and in designing more interactive digital learning. The pretest confirmed that teachers' initial competency was in the low category, especially in the TPACK and technology integration aspects. After the training, teachers demonstrated improved skills in developing digital lesson plans, creating AI-based automated teaching media, and implementing digital assessments in their learning. Teacher reflections demonstrated a shift in pedagogical behavior toward more creative, responsive, and technology-based practices. The PAR cycle was effective in strengthening digital readiness and enhancing teacher self-efficacy. This program demonstrated that practice-based interventions, ongoing mentoring, and community collaboration can accelerate the transformation of MI teachers' digital competencies in a contextual and measurable manner.